Even integers differ by two.
If 3s is even, the even just below 3s is (3s -2) and the even just above 3s would be (3s+2)
so
you must find product :
( 3s - 2 ) ( 3 s ) ( 3 s + 2 ) =
( 3 s * 3 s - 2 * 3 s ) ( 3 s + 2 ) =
( 9 s ^ 2 - 6 s ) ( 3 s + 2 ) =
9 s ^ 2 * 3 s + 9 s ^ 2 * 2 - 6 s * 3 s - 6 s * 2 =
27 s ^ 3 + 18 s ^ 2 - 18 s ^ 2 - 12 s =
27 s ^ 3 - 12 s
Answer C
Suppose 3s represents an even integer. What polynomial represents the product of 3s, the even integer that comes just before 3s, and the even integer that comes just after 3s?
A. 27s^3 + 12s
B. 27s^3 - 3s
C. 27s^3 - 12s
D. 3s^3 - 12s
My calculations are telling me C, but I'm second guessing myself!
1 answer